Lithium compounds in organic synthesis : from fundamentals to applications - Luisi, Renzo; Capriati, Vito (Weinheim, Germany : Wiley-VCH Verlag, 2014)
This unique book covers fundamentals of organolithium compounds and gives a comprehensive overview of the latest synthetic advances and developments in the field. Part I covers computational and spectroscopic aspects as well as structure-reactivity relationships of organolithiums, whereas Part II deals with new lithium-based synthetic methodologies as well as novel synthetic applications of functionalized lithium compounds. A useful resource for newcomers and active researchers involved in organic synthesis, whether working in academia or industry!
Includes bibliographical references at the end of each chapters and index.
Description based on online resource; title from PDF title page (ebrary, viewed March 20, 2014).
Keywords: Cyclic compounds; Lithium compounds; Organic compounds -- Synthesis; SCIENCE / Chemistry / Organic; Cyclic compounds; Lithium compounds; Organic compounds -- Synthesis; Electronic books; Electronic books